Proposing efficient new pendant group polymer electrolyte membranes for fuel cells: a computational study - Mane, Manoj V.; Vanka, Kumar (Journal of Physical Chemistry C, 2014)
There is a need to develop new membranes for fuel cells that can conduct protons with high efficiency and at high temperatures. This paper reports a theoretical study of proton transfer barriers in newly proposed polymer electrolyte membranes (PEMs), having pendant nitrogen containing crown ether groups on an alkyl backbone. The proton transfer in the proposed pendant group PEMs would occur without the need of an external agent such as water or phosphoric acid, and without the need for the pendant groups to rotate and reorient themselves after each proton transfer. The current study shows that this would make the proposed PEMs very efficient, with low proton transfer barriers. This has been seen to be true for a range of different PEM cases considered, differing in the number of linker atoms in the alkyl backbone and in the number of nitrogens contained in each pendant group, thus, indicating the potential of the proposed structures as PEMs for fuel cells.